Influence of high-temperature diffusion annealing on wear resistance of plasma coating ТiC-Ni-Cr - Шевченко, Алексей Леонидович; Киндрачук, Мирослав Васильевич; Башта, Александр Васильевич; Ищук, Наталия Владимировна (Eastern-European Journal of Enterprise Technologies, 2013)
The possibility of improving the quality of plasma coating of TiC-Ni-Cr system, deposited on titanium alloy (α+β), through high-temperature diffusion annealing is considered in the paper. Some results of researches in the field of tribology are given. The main objective of the research is improving physical, mechanical, tribological and technical properties of plasma coating of TiC-Ni-Cr system on titanium alloy Ti-5Al-5Mo-5V-1Fe-1Cr, using high-temperature diffusion annealing. When conducting researches a complex technique was used in the paper, which includes studying the composition, structure and properties of plasma coating and counterbodies using modern physical and chemical methods of analysis, and also determining their tribological properties in conditions of unlubricated sliding friction in the air. The given technology of improving plasma coating quality leads to wear reduction of coating and counterbody, allowing overall control of friction pair properties. The reason for increased wear resistance of plasma coating after high-temperature diffusion annealing is decreased fragility and increased ductility of structural components, as well as increased ability to form tribological structures. The research results can be applied by design engineers when designing various machine parts and mechanisms made of titanium alloys.